Therapeutic Effects of Traditional Chinese Medicine for Patients With Coronary Heart Disease After Treatment of Revascularization: A Prospective Cohort Study in the Northern of China - Lv, Chunxiao; Cheng, Zuozhang; Yu, Hao; Du, Huiqing; Zhao, Yingqiang; Liu, Yujie; Zhang, Junhua; Gao, Sheng; Liu, Ruifeng; Huang, Yuhong (Frontiers in Cardiovascular Medicine, 2021)
Aim: To investigate the compliance and the outcome of Traditional Chinese Medicine (TCM) in patients with coronary heart disease (CHD) after treatment of revascularization. Methods: In this prospective cohort study, non-exposure group (NEG), low-exposure group (LEG) and high-exposure group (HEG) were divided after 2 years’ follow-up. The primary outcome was a composite of death from cardiovascular causes, or non-lethal myocardial infarction, or heart transplantation or stroke. Time-to-event data were evaluated using COX regression with hazard ratios (HRs) and 95% confidence intervals. Then, the two-sided P values were calculated using the Cox models. In order to indicate the therapeutic effects of TCM on the CHD after revascularization, the survival analysis and the nest case-control study were conducted separately. Results: There were 1003 CHD patients enrolled, 356 patients (35.49%) didn’t choose the TCM, 379 patients (37.79%) used the TCM seldom, only 268 patients (26.72%) used TCM regularly. 653 patients with revascularization participated in the prospective cohort study. Over the duration of the trial, the primary endpoints occurred in 12 (4.35%), 11 (4.80%), 2 (1.35%) patients in NEG, LEG and HEG, while the secondary endpoints occurred in 84 (30.43%), 57 (24.89%), 15 (10.14%) patients in NEG, LEG and HEG, respectively. The occurrence time of secondary endpoint events in HEG were significantly postponed (P < 0.001) compared with the other cohorts. The COX regression indicated the HRs in the primary endpoints, the secondary endpoint events, MACCE and the composite endpoint events for HEG were all around 0.3 (P < 0.05) and HRs for LEG were all around 0.8. The results of nest case-control study showed the TCM exposure was significantly different between the cases and controls in the secondary endpoints (P< 0.05), while no significant difference in the primary endpoints (P > 0.05), but the percentage of HEG in the cases was extremely lower than the controls. Conclusion: The HEG-TCM may improve the outcomes of CHD patients after treatment of revascularization. Registration: URL:http://www.chictr.org.cn. Unique identifier: ChiCTR-OOC-17012995.